Modeling and control of a flapping wing robot. (March 2019) - Bakhtiari, Abdolbaghi; Ehtemadi Haghighi, Shahram; Maghsoudpour, Adel
The dynamics and control of a flapping wing robot are studied in this paper which helps to develop a complete dynamic model for the robot consisting of tail effects and also enhance the path tracking control of the robot. In the first part of the paper, the aerodynamic model of the wings is presented, and an aerodynamic force model for the tail is introduced which includes the leading edge suction effects. An experiment is also carried out on a flapping wing robot in a laboratory environment to evaluate the forces on the tail and its result will be compared with the results of the model presented for the tail. In the second part, a controller is designed for the robot. This controller uses the nonlinear dynamic inversion method to solve the nonlinear equations of the control system. The experimental results of the tail forces agree well with the theoretical predictions and reveal that the tail aerodynamics are affected by leading edge suction. Also, simulation results show that the competence performance and convergence performance of the designed controller are obtained.